Memory and the lifespan of human T lymphocytes. - Beverley, P; Michie, C; Young, J (1993)
The properties of human CD45RA and CD45R0 T cells are described. CD45R0 cells respond to recall antigens and provide help for B lymphocytes. They produce a wide variety of cytokines including IL-2, IL-4 and IFN-gamma. CD45RA T cells respond poorly to recall antigens and produce mainly IL-2. The phenotype of CD45R0 cells suggests that they may be in cycle and in vivo data shows that they have a short lifespan while CD45RA cells are long lived. The lineage relationship of the two subsets is not clear but in vivo and in vitro evidence suggests bidirectional conversion between CD45RA and CD45R0 phenotypes.